Prevalence of shiga toxin-producing Escherichia coli O157, O26 and O111 in milk, meat and faeces of cattle, sheep and pigs slaughtered in Benin - BOKO, K. Cyrille (My University, 2020)
Objectives: The study aimed to search for E. coli O157 and non-O157 in milk, meat and faeces of cattle, sheep and pigs slaughtered in Cotonou. Methodology and Results: One hundred and Seventy-Five (175) samples including 25 meat, 25 faeces per species and 25 milk from cattle were analysed for E. coli O157; O26 and O111 and the virulence genes were identified by PCR. The SAS software (1998) and the bilateral Z test were used to calculate and compare the identification frequencies. E. coli O157 was identified in 4% of cattle faeces, 4% of sheep faeces, and 20% of beef and, in 20% of milk samples. E. coli O26 was identified in 12% of cattle faeces and, in 8% of beef samples. E. coli O111 was identified at frequencies of 8%, and 12% in faeces of sheep and pigs, respectively. The eae gene was detected in 4% of beef, ovine meat, milk, pig faeces and in sheep faeces. stx1 was detected in 8% of milk, and in 4% of bovine and sheep faeces. The strains possessing the gene were all of E. coli O157 with the exception of one from pig faeces identified as O111. Conclusions and application of findings: The presence of these serogroups of E. coli with virulence genes poses a real food safety problem in Benin. This study findings must be taken into account for risk assessment and management related to the consumption of food of animal origin
Keywords: Benin; E. coli O157; O26; O111; faeces; meat; milk